Carboxylated polyamidoamine dendron-bearing lipid-based assemblies for precise control of intracellular fate of cargo and induction of antigen-specific immune responses. (8th March 2021) - Yuba, Eiji; Sugahara, Yoshikatsu; Yoshizaki, Yuta; Shimizu, Takeyuki; Kasai, Michiyuki; Udaka, Keiko; Kono, Kenji
Abstract : Carboxylated polyamidoamine dendron lipid-containing liposomes induced precisely controlled content release within intracellular organelles, which induced antigen-specific cellular and humoral immune responses, leading to antitumor effects. Abstract : For the establishment of advanced medicines such as cancer immunotherapy, high performance carriers that precisely deliver biologically active molecules must be developed to target organelles of the cells and to release their contents there. From the viewpoint of antigen delivery, endosomes are important target organelles because they contain immune-response-related receptors and proteins of various types. To obtain carriers for precision endosome delivery, a novel type of polyamidoamine dendron-based lipid having pH-sensitive terminal groups was synthesized for this study. Liposomes were prepared using these pH-sensitive dendron-based lipids and egg yolk phosphatidylcholine. Their pH-responsive properties and performance as an endosome delivery carrier were investigated. pH-Sensitive dendron lipid-based liposomes retained water-soluble molecules at neutral pH but released them under weakly acidic conditions. Particularly, liposomes containing CHexDL-G1U exhibited highly sensitive properties responding to very weakly acidic pH. These dendron lipid-based liposomes released the contents specifically in the endosome. The timing of content release can be controlled by selecting pH-sensitive dendron lipids for liposome preparation. Significant tumor regression was induced in tumor-bearing mice by the administration of CHexDL-G1U-modified liposomes containing the model antigenic protein. Furthermore, CHexDL-G1U-modified liposomes induced WT1 tumor antigenic peptide-specific helper T cell proliferation. The results demonstrate that dendron lipid-based liposomes are useful as a potent vaccine for cancer immunotherapy.